THE RELATIONSHIP OF THE MORPHOMETRIC CHARACTERISTICS OF RUPTURED CEREBRAL ANEURYSMS TO PATIENTS’ AGE - A. L. Rogozin; I. E. Poverennova (Вестник рентгенологии и радиологии)
Objective. To investigate the morphological characteristics of ruptured aneurysms in a group of patients under and over 50 years of age. Material and methods. The investigation enrolled 123 people with ruptured saccular cerebral aneurysms, in whom digital subtraction angiography was carried out in 2011 to 2015. The study took into account the localization of aneurysms, the diameter of the aneurysm dome, the diameter of the aneurysm neck, the axial size of the aneurysmal sac, the distance from the aneurysm neck plane to the aneurysm dome measurement plane, dome-to-neck ratio, axial dimension-to-neck diameter ratio, and aneurysm volume. Results. The diameter of the aneurysm dome (Mann–Whitney U (60; 63)=1384.0; p=0.01), that of the aneurysm neck (U (60; 63) = 1283; p=0.002), aneurysm volume (U (60;63) = 1244.5; p=0.001) were statistically significantly higher in the older age group with a positive correlation with the age of patients. Conclusion. The older age group patients with ruptured cerebral aneurysm had high values of dome and neck diameters and aneurysm volume with a positive correlation between these indicators and the age of patients.